2010
DOI: 10.4103/0970-9290.66633
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency of toluidine blue with Lugol′s iodine in oral premalignant and malignant lesions

Abstract: Lugol's iodine when used with toluidine blue helped in delineating the inflammatory lesions and was the mean source in determining clinically the degrees of differentiation of malignant lesions as the poorly differentiated malignant lesions without glycogen content failed to show Lugol's iodine retention. Toluidine blue with Lugol's iodine can be used as a pretherapeutic assessment of the biologic aggressiveness of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 15 publications
3
30
1
3
Order By: Relevance
“…Considering the inherent limitations of toluidine blue as a diagnostic test our results are in accordance with other studies (Epstein et al, 1997;Nagaraju et al, 2010;Chaudhari et al, 2013). However, results were different from other studies (Myers, 1970;Mashberg and Feldman, 1988) who observed specificity to be much higher 100% and 95% respectively.…”
Section: Discussionsupporting
confidence: 62%
“…Considering the inherent limitations of toluidine blue as a diagnostic test our results are in accordance with other studies (Epstein et al, 1997;Nagaraju et al, 2010;Chaudhari et al, 2013). However, results were different from other studies (Myers, 1970;Mashberg and Feldman, 1988) who observed specificity to be much higher 100% and 95% respectively.…”
Section: Discussionsupporting
confidence: 62%
“…The authors concluded that Lugol's iodine had less sensitivity in identifying oral malignant and dysplastic lesions but it had greater specificity. Moreover, in another study, 30 subjects with clinically suspicious oral PMDs and 30 subjects with clinically suspicious malignant lesions were stained consecutively with TB and Lugol's iodine, the overall sensitivity in detecting dysplasia or malignant lesions was 92.7% while the specificity was 60% (Nagaraju et al 2010). Most of the studies consulted found the Lugol's iodine might have great potential for oral PMDs and oral cancer screening.…”
Section: Lugol's Iodine Stainingmentioning
confidence: 99%
“…The acetic acid does not affect the mature, glycogen-producing epithelium because the acid does not penetrate below the outer one-third of the epithelium [12]. The cells in this region have very small nuclei and a very large amount of glycogen [12].…”
Section: Staining Procedures Acetic Acid Washmentioning
confidence: 99%
“…The cells in this region have very small nuclei and a very large amount of glycogen [12]. Dysplastic cells are the ones which are most affected.…”
Section: Staining Procedures Acetic Acid Washmentioning
confidence: 99%
See 1 more Smart Citation